Nursing practice in children healthcare at a basic health unit (Revista Latino-Americana de Enfermagem, 2003)
This study aimed at identifying nursing actions in the follow-up of growth and development of children under five years old who were assisted at two Basic Health Units in Franca, Brazil. The empirical study was based on observation of nursing activities in the vaccination, pre-consultation, post-consultation and newborn screening test collection sectors, using video recording. We concluded that basic follow-up actions concerning growth and development, breastfeeding stimulation, food orientation, vaccination and prevalent disease prevention are permeating nursing care, although in a fragmented way in communication and ties established with clients.